Rapid, ultrasensitive, and highly specific identification of Brucella abortus utilizing multiple cross displacement amplification combined with a gold nanoparticles-based lateral flow biosensor - Yang, Xinggui; Wang, Yue; Liu, Ying; Huang, Junfei; Wei, Xiaoyu; Tan, Qinqin; Zeng, Xiaoyan; Ying, Xia; Li, Shijun (Frontiers in Microbiology, 2022)
Brucella abortus (B. abortus) as an important infectious agent of bovine brucellosis cannot be ignored, especially in countries/regions dominated by animal husbandry. Thus, the development of an ultrasensitive and highly specific identification technique is an ideal strategy to control the transmission of bovine brucellosis. In this report, a novel detection protocol, which utilizes multiple cross displacement amplification (MCDA) combined with a gold nanoparticles-based lateral flow biosensor (AuNPs-LFB) targeting the BruAb2_0168 gene was successfully devised and established for the identification of B. abortus (termed B. abortus-MCDA-LFB). Ten specific primers containing engineered C1-FAM (carboxyfluorescein) and D1-biotin primers were designed according to the MCDA reaction mechanism. These genomic DNA extracted from various bacterial strains and whole blood samples were used to optimize and evaluate the B. abortus-MCDA-LFB assay. As a result, the optimal reaction conditions for the B. abortus-MCDA-LFB assay were 66 °C for 40 min. The limit of detection (LoD) of the B. abortus-MCDA-LFB was 10 fg/μl (~3 copies/μl) for genomic DNA extracted from pure cultures of B. abortus isolate. Meanwhile, the B. abortus-MCDA-LFB assay accurately identified all tested B. abortus strains, and there was no cross-reaction with non-B. abortus pathogens. Moreover, the detection workflow of the B. abortus-MCDA-LFB assay for whole blood samples can be completed within 70 min, and the cost of a single test is approximately 5.0 USD. Taken together, the B. abortus-MCDA-LFB assay is a visual, fast, ultrasensitive, low-cost, easy-to-operate, and highly specific detection method, which can be used as a rapid identification tool for B. abortus infections.